A Spectral Triple for a Solenoid Based on the Sierpinski Gasket - Aiello, Valeriano; Guido, Daniele; Isola, Tommaso (Symmetry, Integrability and Geometry: Methods and Applications, 2021)
The Sierpinski gasket admits a locally isometric ramified self-covering. A semifinite spectral triple is constructed on the resulting solenoidal space, and its main geometrical features are discussed.